Progression of the PI3K/Akt signaling pathway in chronic obstructive pulmonary disease - Liu, Yanhui; Kong, Haobo; Cai, Heping; Chen, Guanru; Chen, Huiying; Ruan, Wenyi (Frontiers in Pharmacology, 2023)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic respiratory disease characterized by a slow progression and caused by the inhalation of harmful particulate matter. Cigarette smoke and air pollutants are the primary contributing factors. Currently, the pathogenesis of COPD remains incompletely understood. The PI3K/Akt signaling pathway has recently emerged as a critical regulator of inflammation and oxidative stress response in COPD, playing a pivotal role in the disease's progression and treatment. This paper reviews the association between the PI3K/Akt pathway and COPD, examines effective PI3K/Akt inhibitors and novel anti-COPD agents, aiming to identify new therapeutic targets for clinical intervention in this disease.